A cadeira de madeira torneada : objeto de desejo doméstico e produção moderna presente na obra "O importuno", de Almeida Júnior - Buzetto, Denise Maria Chane (2014)
This paper addresses the thematic paintings of interiors, its object of study is the presence of the chair bent wood type Thonet , an inserted object in domestic work The Annoying, José Ferraz de Almeida Júnior (1859-1899), as index, a contamination of th